Modulation versus Templating: Fine‐Tuning of Hierarchally Porous PCN‐250 Using Fatty Acids To Engineer Guest Adsorption. (1st August 2019) - Kirchon, Angelo; Li, Jialuo; Xia, Fangqing; Day, Gregory S.; Becker, Benjamin; Chen, Wenmiao; Sue, Hung‐Jue; Fang, Yu; Zhou, Hong‐Cai
Abstract: Modulation and templating are two synthetic techniques that have garnered significant attention over the last several years for the preparation of hierarchically porous metal–organic frameworks (HP‐MOFs). In this study, by using fatty acids with different lengths and concentrations as dual‐functional modulators/templates, we were able to obtain HP‐MOFs with tunable mesopores that exhibit different pore diameters and locations. We found that the length and concentration of the fatty acids can determine if micelle formation occurs, which in turn dictates the porosity of the resulting HP‐MOFs. The HP‐MOFs with different mesopores differed in their performance in gas uptake and dye adsorption, and the structure–performance relationships were ascribed to the pore diameters and locations. This approach could provide a potentially universal method to efficiently introduce hierarchal mesopores into existing microporous MOF adsorbents with tunable properties. Abstract : Das Beste aus beiden Welten : Fettsäuren wurden als duale funktionale Modulatoren/Template verwendet, um hierarchisch poröse Metall‐organische Gerüste (HP‐MOFs) aufzubauen. Die Länge und Konzentration der Fettsäure bestimmt, ob Mizellenbildung und damit die Porosität des resultierenden HP‐MOFs auftreten kann (siehe Bild). HP‐MOFs mit verschiedenen Mesoporen unterschieden sich in ihrer Leistung bei der Gasaufnahme und Farbstoffadsorption.